Assessing the impact of water treatment residuals and rice straw compost on soil physical properties and wheat yield in saline sodic Soil. Issue 18 (10th October 2020) - Ibrahim, Mahmoud; Mahmoud, Esawy; Ibrahim, Doaa
ABSTRACT: Rice straw compost (RC) and water treatment residuals (WTR) can improve both organic wastes recycling and soil physical properties of salt-affected soils. Therefore, the aim of this study was to test the effect of RC and its mixture with WTR on some physical properties of the saline-sodic soil, and wheat yield. The treatments were RC, WTR, and RC + WTR mixture at rates of 12 and 24 t ha −1 . The results indicated that the application of RC alone or combined with WTR significantly increased drainable porosity (DP), total porosity (TP), mean weight diameter (MWD) and total water-stable aggregates (WSA) as compared to control. The increase in soil DP under the 24 t of WTR ha −1 was 64.7% greater than the control treatment. The mixtures of RC +WTR gave better results in increasing the dry weight and grain yield, especially the rate of 24 t of RC +WTR (1:2) ha −1 soil as compared to adding them individually. The experimental results concluded that the WTR + RC mixture can be used as a promising strategy to increase wheat yield and improve the efficiency of recycled rice straw and WTR on the physical properties of saline-sodic soils.